Stability Control Design of Sigma Class Ship Firing Mode using Fuzzy Gain Scheduling-PID - Munadhif, Ii; Aisjah, Aulia Siti; Masroeri, A A (IPTEK Journal of Proceedings Series, 2015)
Sigma class ship of Hasanuddin 366 is one of Indonesian battle ship. When the ship operates, shipwreck can be happened because impact force disturbance can increase the angle of yaw and roll. In this research, the system of rudder roll stabilization is designed to keep the ship heading/yaw and decrease the roll angle using ship nonlinear dynamic model of 4 degree of freedom (DOF) that contains surge, sway, yaw, and roll.Â  Fuzzy gain schedulingâ€“PID (FGS-PID) controller is used to control rudder angle as the steering control. The value of the cannon impact force disturbance is 1062.525 Newton with angle variation of 30o from the direction of ship surge. The FGS-PID controller is compared with the PID Ziegler Nichols (PID-ZN) controller as reliability test. According to simulation result, the FGS-PID controller is better than PID-ZN in keeping the heading and decreasing the roll. The performance of FGS-PID controller with heading input of 20o and 30o is compatible with the stability parameter of IMO (International Maritime Organization).